Joking asides: the theory, analysis, and aesthetics of humor - Oring, Elliott, author; Utah State University Press, publisher (Colorado State University. Libraries, 2016)
Oring analyzes key contemporary approaches to the study of humor and addresses controversial topics with new empirical data and insight. He tests appropriate incongruity against other major positions in the field, including Semantic Script Theory, the General Theory of Verbal Humor, Conceptual Integration Theory, and Benign Violation Theory.--Provided by publisher.
What Freud actually said about jokes -- Parsing the joke: the general theory of verbal humor and appropriate incongruity -- Blending and humor -- On benign violations -- Humor and the discovery of false beliefs -- Framing Borat -- Risky business: political jokes under repressive regimes -- Listing towards lists: jokes on the Internet -- What is a narrative joke? -- Demythologizing the Jewish joke -- The ridiculous to the sublime: joke and art -- Contested performance and joke aesthetics.
Keywords: Wit and humor -- History and criticism; Jewish wit and humor -- History and criticism; Wit and humor -- Psychological aspects